Title: Conceptualizing Organizational Resilience at an SME level - Ahmad Khan (Lecturer), Talha Zubair; Farooq, Waqas; Siddiqi, Ahmed Faisal; Shabbir, Muhammad Salman; Sulaiman, Mohammed Ali Bait Ali (International Journal of Psychosocial Rehabilitation, 2020)
There seems to have greater interest in studying organizational resilience in recent years. Organizational resilience has mostly been understood as a unique organizational resource that can be deployed under stiff environmental conditions in order to survive, a traditional conceptualization of the subject phenomenon that put emphasis on the resources-based perspective. However, there seems to be less consensus over the conceptualization of organizational resilience specifically at small medium enterprise level of analysis. We present a dynamic shift from a traditional resource-based view of organizational resilience to a dynamic capability’s perspective. Our findings suggest that organizational resilience necessarily entails dynamic processes of sensing, reconfigurations, and organizational learning that not only focuses on crises specific reactive strategies but also on the proactive aspects of preparedness.